Pengembangan Media Komik Digital Berbantuan Make Beliefs Comix pada Materi Aturan di Sekolah Kelas II SDN 1 Moyoketen - Ronatama Simangunsong; Nugrananda Janattaka (Departement of Mathematics Education, 2024)
Research on the development of digital comic media assisted by make beliefs comix is motivated by the less than optimal use of learning media, because teachers only use student books to support the learning process. Media is made to provide solutions to the lack of variety of learning media. Digital comic media assisted by make beliefs comix material rules in school in digital form and more focused on learning Pancasila Education material rules at school. The research used the Analysis, Design, Development, Implementation, Evaluation (ADDIE) development model. The validity of this media development is determined from the validation results of media experts, material experts, and linguists. The results of the feasibility trial of digital comic media assisted by make belief comix media experts get a percentage score of 86% with the category